Comparative Study of Fuzzy Logic, Artificial Neural Network, and Neuro-Fuzzy System in Medical Diagnostic - An Approach towards a Medical Expert System - Kolle, Harvey Ngoe (Jihočeská univerzita, 2023)
This study compares the performance of three artificial intelligence techniques (fuzzy logic, artificial neural networks, and neuro-fuzzy systems) in the medical diagnosis of diabetes mellitus, heart disease, and hepatitis B. Medical expert systems were developed using these techniques and evaluated on medical datasets. The results show that neuro-fuzzy systems demonstrate the best performance overall and are the most promising approach for developing accurate and efficient medical expert systems.
Comparative Study of Fuzzy Logic, Artificial Neural Network, and Neuro-Fuzzy System in Medical Diagnostic - An Approach towards a Medical Expert System
Keywords: fuzzy logic; artificial neural networks; neuro-fuzzy systems; medical diagnosis; expert system.; fuzzy logic; artificial neural networks; neuro-fuzzy systems; medical diagnosis; expert system.